Enhancing Cybersecurity: Applying Advanced Analytic Techniques (Journal of The Colloquium for Information Systems Security Education, 2016)
This paper describes several techniques for enhancing cybersecurity and information assurance. Specifically, the paper describes the vulnerability of public and private sector enterprises to advanced and persistent cyber-attacks. To counter these attacks the paper proposes an innovative approach for enhancing cybersecurity by fusing cyber forensics, data mining of big data, and advanced analytic techniques to improve the operational cybersecurity posture of all enterprises operating in the cyber space environment. The intent of the paper is to advance the knowledge in the critical areas of cybersecurity and information assurance by suggesting the creation of an integrated cybersecurity framework to guide analysis of intelligence left behind by attackers; monitoring of networks and systems to identify persistent threats; and eventually using advanced analytics to anticipate and prevent future attacks.
Keywords: Advanced Analytics; Big Data; Cyber Forensics; Cybersecurity; Information Assurance